THE INFLUENCE OF TIME MANAGEMENT ON ACADEMIC PROCRASTINATION MEDIATED BY SELF-REGULATED LEARNING IN THE COVID-19 PANDEMI AT SMK PGRI 1 JAKARTA - Ningsih, Rifa Silviaty; Usman, Osly; Marsofiyati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of time management on academic procrastination mediated by self-regulated learning during the COVID- 19 pandemic in students of SMK PGRI 1 Jakarta. The research method used in this research is a survey or questionnaire distribution using a Likert scale. The sample used in this study obtained 245 respondents from SMK PGRI 1 Jakarta students. Based on the research conducted, the results show that there is a positive and significant effect of self-regulated learning in mediating the indirect effect of time management on academic procrastination.